2014
DOI: 10.3389/fncom.2014.00019
|View full text |Cite
|
Sign up to set email alerts
|

Subtractive, divisive and non-monotonic gain control in feedforward nets linearized by noise and delays

Abstract: The control of input-to-output mappings, or gain control, is one of the main strategies used by neural networks for the processing and gating of information. Using a spiking neural network model, we studied the gain control induced by a form of inhibitory feedforward circuitry—also known as “open-loop feedback”—, which has been experimentally observed in a cerebellum-like structure in weakly electric fish. We found, both analytically and numerically, that this network displays three different regimes of gain c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 54 publications
0
17
0
1
Order By: Relevance
“…Therefore the neurons are for long time active and unaffected by the other neurons, however when they receive large inhibitory PSPs they remain silent for long periods. It has been shown that heterogeneity and noise can increase the information encoded by a population counteracting the correlation present in neuronal activity [35][36][37][38][39]. However, it remains to clarify how disorder (neural heterogeneity and randomness in the connections) and delay should combine to enhance information encoding.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the neurons are for long time active and unaffected by the other neurons, however when they receive large inhibitory PSPs they remain silent for long periods. It has been shown that heterogeneity and noise can increase the information encoded by a population counteracting the correlation present in neuronal activity [35][36][37][38][39]. However, it remains to clarify how disorder (neural heterogeneity and randomness in the connections) and delay should combine to enhance information encoding.…”
Section: Discussionmentioning
confidence: 99%
“…We find a major role for inhibition in shaping both the trial‐to‐trial reproducibility of the post‐synaptic response to ongoing natural stimuli, and the magnitude of spike rates – effects that inhibition could manifest by altering the correlation structure of the network. The gain of responses could also be modulated directly by feed‐forward inhibition (Mejias et al ., ). Input–output mappings even in single neurons are not static over time or behavioral conditions (Kozlov & Gentner, ), and our results demonstrate that inhibition is poised to provide flexible control over these response characteristics under natural conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent observation for a stationary renewal process at any time, the latest available information, is the elapsed time since the most recent event. Many models have been proposed to explain multiplicative gain or sensitivity adjustments and normalization of activity levels across neural populations (Bastian, 1986; Beck, Latham, & Pouget, 2011; Capaday, 2002; Carandini & Heeger, 2012; Eliasmith & Martens, 2011; Louie, Khaw, & Glimcher, 2013; Mejias, Payeur, Selin, Maler, & Longtin, 2014; Nelson, 1994; Olsen, Bhandawat, & Wilson, 2010; Silver, 2010), and we will not consider possible mechanisms for these operations in the vestibular system beyond noting that it is widely accepted that neurons are capable of such computations. The key additional computational capability that neurons would require to implement dynamical Bayesian inference in the vestibular system is the ability to compute parameter likelihoods given the elapsed time since the most recent event.…”
Section: Resultsmentioning
confidence: 99%